AGGRESSIVE VS. DISCRETE MARKETING - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2019)
In the modern world, everything is for sale, starting from goods and services, through ideas and information, to people, as experts in certain jobs. Nothing is out of the market system, and a well-known password that "everyone and everyone has their price", it seems that before, as it is now, it has its full valorization. Why is it so and why are people trying to get everything they have to market, or is this behavior the result of a general race for profit? Perhaps people evolved in their endeavors to get economically as soon as possible and occupy the best market position. In that sense, the fact is that there really is little chance of winning a superior financial position. The only area that can provide success, at least in the short run, is marketing, but not any, but an entirely new type of marketing that evolved in parallel with people’s efforts to secure their economic interests - aggressive marketing. Reversed by this type of marketing, but parallel to it, discrete marketing develops, which uses its techniques again to gain and motivate people to opt for shopping.